Medicinal Plants used in the Treatment of Hepatitis in BoboDioulasso: Studying the Availability and Analyzing the Phytochemical Properties of Combretum micranthum G. Don and Entada africana Guill. et Perr. - Bernice, Dakio; Jean, Bangou Mindiédiba; Paulin, Ouoba; Hermann, Ouoba Yempabou; Samson, Guenné; N.T., Meda Roland; Kader, Zangré Abdoul; Romaric, Tiendrebeogo; Ouédraogo, Anicet Georges (European Scientific Journal, ESJ, 2020)
This paper focuses on studying the inventory of the medicinal plants used in hepatitis care in Bobo-Dioulasso and evaluating their availability in local vegetation and their phytochemical properties. To achieve this objective, several approaches were developed which include: (1) an ethnobotanical survey among 111 traditional health practitioners (THP); (2) a dendrometric study to evaluate the abundance and spatial distribution of these species in Dindérésso Classified Forest; and (3) an evaluation of polyphenolic compounds and antioxidant activity of the two most quoted species roots using three methods such as anti-DPPH*, anti-FRAP, and antiABTS. The results show that Entada africana and Combretum micranthum were the most quoted species among 40 species used in the treatment of liver disease. The availability study revealed that juvenile and adult individuals of E. africana are frequent in woody savannah, shrubby savannah, and grassy savannah. As for juvenile and adult C. micranthum individuals, they are only frequent in wooded savannah (RI<60%). These populations are therefore declining due to anthropogenic pressure. Phytochemical analysis reveal polyphenols contents of 37.91 and 20.71 mg EAG/100 mg respectively for C. micranthum and E. africana and flavonoids contents of 0.85 ± 0.09 and 0.66 ± 0.05 mg EQ/100 mg respectively for C. micranthum and E. africana. Finally, the results show that there is an anti-oxidant activity for the two species. There were about 198 and 13 μmol EAA/g for the two species i.e., ABTS and DPPH, respectively. The results show that the antioxidant activity could partially justify the traditional use of this plant.